The Political Communication Tactics of the National Democratic Party (NasDem) for Winning the Legislative Election - Aida Farichatul Laila; Khoirul Muslimin; Lukman Hakim (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2022)
This article discusses the political communication strategy of a party, especially the National Democratic Party (NasDem) in Central Java in the 2019 Legislative Election. This study uses the Elaboration Likelihood ModelTheory from Petty and Cacciopo, when the persuasion of messages in the campaign can be accepted by the public so that they can win the 2019 Legislative Election contestation. This study uses a postpositivism paradigm, with qualitative descriptive research methods and triangulation of data sources, while this research focuses on the candidates for members of the NasDem Party. They are now legislative members in the DPRD of Central Java Province. The results of this study indicate that the Political Communication Tactics used by the Central Java NasDem Party in winning the 2019 Election Contestation was communicating with a traditional approach by personally meeting the cloud community, organizations community, community leaders, Islamic figures (Kiai), former officials, RT and RW. Those ways were carried out by the model of house visit, 'nguwongke uwong',. This study indicates that three legislative candidates who are currently sitting in the DPRD of Central Java have been elected.